Tourism Marketing Promotion Strategy which Inflf luence Tourism Motivation to Generation Z in Bangkok Metropolitan Region - ศุทธิเวทิน พรรษกฤช; บัวสอน ภูเกริก (Business Administration and Management Journal Review, 2019)
The research is the study Tourism Marketing Promotion Strategy Which Influence Tourism Motivation to Generation Z in Bangkok Metropolitan Region. The objectives of this research are (1) to study the influence of tourism marketing promotion strategy to motivate generation z to travel in Bangkok Metropolitan region and (2) to study guidelines for tourism marketing promotion strategy of generation z in Bangkok Metropolitan region. That a researcher used mixed method to collect and analyze the data which were (1) quantitative research to collect 420 questionnaires from whom are 16-20 years old in Bangkok, Nakhon Pathom, Nonthaburi, Pathum Thani, Samut Prakan and Samut Sakhon for analyzing by frequency distribution, percentage, average, standard deviation and Multiple Regression. (2) qualitative research collecting by in-depth interview with 28 people who are government executives, private sector executives and entrepreneur and generation z to analyze by content analysis. The results of this study found (1) tourism promotion strategy influences the motivational travel of generation z in Bangkok Metropolitan region at the statistical significant level of 0.01 and (2) guidelines for tourism promotion strategy of generation z in Bangkok Metropolitan region are social media advertising, channels newspapers, magazines and social media towards public relations channels, online personal selling channels and price discounts via promotion discount sale promotion channels.